Using More Sophisticated Technology to Teach Mathematics (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2018)
Over time, the debate about using technology in the classroom has evolved as much as the technology itself. Not only has the role of technology grown and shifted in the classroom, but also the level of technological sophistication has changed the way these tools are used. Employing these tools in the mathematics classroom allows students to no longer take a somewhat passive role, treating technology as either their master or servant. Rather, these tools allow the technology to become the students’ partner or an extension of themselves. In addition, students can now engage in the role of active learners by producing and/or publishing content previously not possible. Even though the TI-83/84 has its place in the mathematics classroom, particularly considering the high-stakes testing relationship, mathematics educators must embrace the ever-growing tools of Web 2.0 to become even more efficient and effective.